MANAJEMEN PELAKSANAAN PEMBIASAAN TILAWAH AL-QUR’AN DALAM MEMBINA SISWA BERKARAKTER RELIGIUS DAN GEMAR MEMBACA (STUDI DESKRIPTIF DI SMK BUDI BHAKTI UTAMA CIBURUY BANDUNG BARAT) - Iman Budiman; Achmad Sanusi; Husen Saeful Insan (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
Characters that must be strived to be born and carried out consistently by students are religious characters and love to read. The facts show that not all students are religious in character and like to read. Lack of manners, manners, mutual respect for each other and sincerity in carrying out prayers, lack of enthusiasm for reading the Qur'an, reading book literacy and digital literacy. The purpose of this study was to obtain an overview and analysis of the management of the implementation of the habituation of recitation of the Qur'an in fostering the religious character and reading pleasure of students. This study uses a qualitative descriptive method using data collection techniques, through interviews, observations and documentation. The conclusion is that the management of the implementation of the habituation of recitation of the Qur'an can foster students with religious character and love to read. This can be proven by the behavior of students in the school environment and outside the school environment showing consistency in reciting the Qur'an, behaving politely, including greetings, performing Duha prayers, mutual respect among friends, respect for teachers and various achievements that have been achieved. in the field of religious extracurricular in PENTAS PAI competitions at the cluster level, sub-district and district level. The results of this study are recommended to be used as comparative study material for researchers personally, as well as for PAI teacher institutions and students